Incremental green certificate towards flexibility incentive for renewable dominated power systems. (1st December 2022) - Xie, Haipeng; Wang, Yun; Ren, Hanyu; Sun, Xiaotian; Bie, Zhaohong
Abstract: In renewable dominated power systems, the primary challenge is how to incentivize the utilization of subsistent renewable energy instead of how to incentivize the investment to expand renewable energy. This paper proposes an incentive policy named incremental green certificate (IGC) to cope with the challenge. The proposed IGC directly transfers voluntary consumers' payment to cover the premium of flexible resources to utilize more renewable energy. To make the IGC cooperative with power markets, a two-stage day-ahead market clearing model is proposed. In the model, the first stage follows on-going power market rules to clear the locational price, and the second stage reschedules the flexible resources to clear the IGC. Also, the incentive compatibility of the proposed policy is demonstrated, and the system dynamic model is built to quantify the long-term influence. Conclusions are drawn from the case studies on modified PJM 5-bus and a real-life provincial power system in China. The IGC would boost the investment of flexible resources, reduce the curtailment of renewable energy, and benefit renewable energy companies in the long term. Highlights: Proposed an IGC policy to reduce the curtailment of highly penetrated green energy. A two-stage market clearance model is proposed to maximize green energy penetration. Proved the incentive compatibility of the IGC policy. Quantified the long-term effect of IGC on flexible resources using system dynamics.